Spatiotemporally resolved black carbon concentration, schoolchildren's exposure and dose in Barcelona. (16th May 2015) - Rivas, I.; Donaire‐Gonzalez, D.; Bouso, L.; Esnaola, M.; Pandolfi, M.; de Castro, M.; Viana, M.; Àlvarez‐Pedrerol, M.; Nieuwenhuijsen, M.; Alastuey, A.; Sunyer, J.; Querol, X.
Abstract: At city level, personal monitoring is the best way to assess people's exposure. However, it is usually estimated from a few monitoring stations. Our aim was to determine the exposure to black carbon (BC) and BC dose for 45 schoolchildren with portable microaethalometers and to evaluate the relationship between personal monitoring and fixed stations at schools (indoor and outdoor) and in an urban background (UB) site. Personal BC concentra‐tions were 20% higher than in fixed stations at schools. Linear mixed‐effect models showed low R 2 between personal measurements and fixed stations at schools ( R 2 ≤ 0.28), increasing to R 2 ≥ 0.70 if considering only periods when children were at schools. For the UB station, the respective R 2 were 0.18 and 0.45, indicating the importance of the distance to the monitoring station when assessing exposure. During the warm season, the fixed stations agreed better with personal measurements than during the cold one. Children spent 6% of their time on commuting but received 20% of their daily BC dose, due to co‐occurrence with road traffic rush hours and the close proximity to the source. Children received 37% of their daily‐integrated BC dose at school. Indoor environments (classroom and home) were responsible for the 56% BC dose.